Phosphonated USY, a promising catalyst for the development of environmentally benign biodiesel (methyl acetate) process - Nandiwale, Kakasaheb Y.; Gopal, Gahana C.; Bokade, Vijay V. (Journal of Energy Chemistry, 2015)
The present study focuses on the evaluation of the potential applicability of Ultra Stable Y (USY) and phosphonated USY (1 wt%-4 wt% phosphorous loading) as heterogeneous catalysts for biodiesel (methyl acetate) production. The synthesized catalysts were characterized by powder X-ray diffraction (XRD), Brunaer-Emmett-Teller (BET) surface area, total acidity by temperature-programmed desorption of ammonia (TPD-NH3) and Fourier Transform Infrared (FTIR) spectra. The performances of catalysts were evaluated for the transesterification of butyl acetate with methanol (a model reaction in biodiesel production). In view to obtain a maximum yield of methyl acetate, the optimization of process parameters such as reactant molar ratio, catalyst loading, reaction temperature and reaction time was performed. All the phosphonated USY catalysts showed higher catalytic activity than the parent USY, which can be attributed to the increase of total acidity due to phosphonation. 2 wt% P/USY (2% phosphorous loaded on USY) exhibited 92% methyl acetate yield with 100% selectivity, which was proved to be a potential catalyst for biodiesel production. The invented catalyst was found to be stable and reusable for five catalytic cycles, demonstrating that it might be a environmentally benign catalytic process.
Keywords: Biodiesel; methyl acetate; phosphonated USY; transesterification